Veronica Mars. The complete third season [videorecording (DVD)] - Bell, Kristen, 1980-; Dohring, Jason; Daggs, Percy (Distributed by Warner Home Video, 2013)
Teenage sleuth Veronica Mars continues her detective work during her first year as a student at Hearst College.